2015
DOI: 10.1590/1809-4392201402954
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and physical attributes and calcium, magnesium, potassium, and phosphorus in the soil of murundu fields in Brazil

Abstract: RESUMO Campos de murundus (CM, Al 3+ and H+Al] and physical [texture and bulk density (Bd)] soil attributes and calculate the organic matter (OM) and nutrient stock (P, Ca, Mg, and K) in soils of FM located in the Guapore River basin in Mato Grosso. Thirty-six sampling points were selected, and soil samples were collected from two environments: the murundu and plain area surrounding (PAS). At each sampling point, mini trenches of 0.5 × 0.5 × 0.4 m were opened and disturbed and undisturbed soil samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It was observed that Pb contents were lower than those reported in the literature for other soils (Pierangeli et al, 2009;Santos & Alleoni, 2013;Pierangeli et al, 2015). This fact may be related to the soil granulometry of these murundus fields: 200 and 250 g of kg -1 of clay in the flat and murundu area, respectively (Santos et al, 2015).…”
Section: +mentioning
confidence: 64%
See 1 more Smart Citation
“…It was observed that Pb contents were lower than those reported in the literature for other soils (Pierangeli et al, 2009;Santos & Alleoni, 2013;Pierangeli et al, 2015). This fact may be related to the soil granulometry of these murundus fields: 200 and 250 g of kg -1 of clay in the flat and murundu area, respectively (Santos et al, 2015).…”
Section: +mentioning
confidence: 64%
“…The low levels of trace elements observed here reflect the source material. These are soils formed from unconsolidated sediments of the Guaporé Formation (Santos et al, 2015), in addition to leaching processes favored by the solubility of the elements (Olivie-Lauquet et al, 2001), which may further decrease the natural levels of these elements in these soils. presented mean values of several elements in native vegetation soils in the state of Mato Grosso.…”
Section: +mentioning
confidence: 99%